Association of Serum Uric Acid and Liver Enzymes in Adults at Tertiary Level Hospital in Bangladesh - Chanda, Manashe; Biswas, Tapos; Amiruzzaman, Molla; Begum, Hasina; Tabassum, Fareeda; Munmun, Sadia Tasnim; Rahman, Ashiqur; Akram, Arifa (Bangladesh Medical Journal, 2024)
The level of serum uric acid (SUA) has been linked to metabolic syndrome, diabetes, and cardiovascular disease. The purpose of this study was to evaluate the relationship between SUA and serum liver enzymes in a Bangladeshi adult population. This cross-sectional study was conducted among apparently healthy adults aged >18 years, from March 2019 to February 2020 at the Department of Biochemistry, Sir Salimullah Medical College (SSMC), Dhaka. SUA, liver enzymes, lipid profile and other biochemical markers were measured in the collected samples by using standard methods. All statistical analyses were performed by using SPSS version 22.0 software and p<0.05 was considered statistically significant. A total of 140 subjects were selected and blood sample were collected for biochemical analysis. Among them 70 were male and 70 were female. Serum uric acid (SUA), Alanine transaminase (ALT), Aspartate aminotransferase (AST) and Gamma-glutamyl transferase (GGT) levels were significantly (p<0.001) higher in male than female group. Pearson’s correlation analysis showed that there were significant positive correlation between SUA and serum ALT, AST, GGT (p<0.001). However, it also showed significant positive correlation between SUA and total cholesterol (TC), triglycerides (TG), low density lipoprotein cholesterol (LDL-C), while negative correlation was found between SUA and high density lipoprotein cholesterol (HDL-C) (p<0.001). The role of SUA in the prediction of elevated liver enzymes showed area under the ROC Curve (AUC) 0.839 for ALT, 0.848 for AST and 0.809 for GGT respectively. SUA is positively related with ALT, AST, GGT in adults. More prospective studies are needed to clarify the complex relationship between SUA and liver enzymes in the general population. Bangladesh Med J. 2022 Sept; 51(3): 18-27